THE HISTORICAL CONNECTION BETWEEN THE GOLDEN RULE AND THE SECOND GREATEST LOVE COMMAND - Stanglin, Keith D. (Journal of religious ethics, 2005)
The golden rule, perhaps the most recognizable moral maxim in Western culture, is an inadequate basis for morality. In light of its flaws as a precept and its apparent lack of moral content, it is initially perplexing that the historic Judeo-Christian tradition has often linked the golden rule with the second greatest command to love one's neighbor as oneself. However, after examining the presuppositions behind this link and investigating the biblical context of these sayings, it is clear that the Judeo-Christian tradition is justified in making this connection. Although the golden rule and the love command should not be conflated and their distinctions should not be abandoned, the biblical intention of the golden rule can only be understood and properly practiced in connection with the love command.